Influence of an Acute Exposure to a Moderate Real Altitude on Motoneuron Pool Excitability and Jumping Performance - Štirn, Igor; Garcia-Ramos, Amador; Feriche, Belen; Strojnik, Vojko; Tomažin, Katja (Frontiers in Physiology, 2022)
The aim of the study was to test whether ascending to a moderate real altitude affects motoneuron pool excitability at rest, as expressed by a change in the H-reflex amplitude, and also to elucidate whether a possible alteration in the motoneuron pool excitability could be reflected in the execution of lower-body concentric explosive (squat jump; SJ) and fast eccentric-concentric (drop jump; DJ) muscle actions. Fifteen subjects performed four experimental sessions that consisted of the combination of two real altitude conditions (low altitude [LA, 690 m], high altitude [HA, 2320 m]) and two testing procedures (H-reflex and vertical jumps). Participants were tested on each testing day at 8h, 11h, 14h and 17h. The only significant difference (p < 0.05) detected for the H-reflex was the higher H-reflex response (25.6%) obtained 15 min after arrival at altitude compared to baseline measurement. In terms of motor behavior, DJ height was the only variable that showed a significant interaction between altitude conditions (LA and HA) and time of measurement (8h, 11h, 14h and 17h) as DJ height increased more during successive measurements at HA compared to LA. The only significant difference between the LA and HA conditions was observed for DJ height at 17h which was higher for the HA condition (p = 0.04, ES = 0.41). Although an increased H-reflex response was detected after a brief (15-20 min) exposure to real altitude, the effect on motorneuron pool excitability could not be confirmed since no significant changes in the H-reflex were detected when comparing LA and HA. On the other hand, the positive effect of altitude on DJ performance was accentuated after six hours of exposure.